Field Trail of F1 Population of Elite Sweet Potato (Ipomoea Batatas (L.) Lam) For Yield and Yield Related Traits in Humid Rainforest of Umudike, Southeastern Nigeria - Harry, Gamaliel I.; Ulasi, Joseph I.; Rosemary, Keyagha E. (European Journal of Applied Sciences, 2023)
Sixty-eight sweet potato progenies developed from one common parent (Ligri PC), including national and local checks varieties (Umuspo 3 and TIS 87/0087) were subjected to two-year field trail under rainfed conditions to identify superior genotypes with high fresh storage root yield, dry matter, starch and vulnerability to Cylas spp. At the National Root Crops Research Institute, Umudike, Southeastern Nigeria during the 2015 and 2016 cropping seasons. Yield and yield related data collected at harvest were subjected to analysis of variance, correlation analysis and principal component analysis. During the first-year trail, LPC/13 produced the highest yield of 22.50 tons/ha while LPC/14 produced the highest yield of 22.56 tons/ha in the second-year trail. LPC/45 had the highest starch content, 68.79 mg100g-1. Total storage root yield was highly significant (P<0.01) and positively correlated with marketable root number (r=0.571), unmarketable root number (r=0.301), marketable root weight (r=0.793) and unmarketable root weight (r=0.481), respectively. Results from this study showed that fourteen (14) genotypes had no observable sweet potato weevil damage, whereas sixteen (16) genotypes had minimal sweet potato weevil damage. Fifteen (15) genotypes recorded moderate damage caused by sweet potato weevil attack. Superior genotypes are recommended to be mass produced for cultivation in the humid rain forest zone of Nigeria and incorporated into sweet potato breeding program for the development of high-yielding and resistant genotypes.